Otimização do tempo de tratamento térmico de nonocristais core e core-shell de LaF3 dopados com íons terra raras - Sousa , Michael Ronnes Medeiros de (2016)
In this work, we investigated the annealing time optimization of core and core-shell LaF3 nanocrystals doped and co-dopados with rare earth ions. To this, several sets of LaF3 samples were synthesized and submitted to thermal treatment (TT) at 500oC for different times [0 (no TT), 5, 10, 30, 90, and 180 minutes]. Structural characterizations using x-ray diffraction, FTIR, and Raman spectroscopy were carried out, and optical characterization by means of luminescence. It was observed that the TT does not change the hexagonal phase of LaF3; the diffraction peaks are enhanced due to crystallinity improvement; and impurities of hydroxyl groups (O-H) and of H2O molecules are significantly reduced. In the core samples, these O-H and H2O vibration modes are more reduced for 180 minutes of TT. However, for the Yb/Er co-doped core and core-shell samples, little or almost no difference was observed in the FTIR results for TT times from 30 minutes. Regarding the optical properties, the emissions increased significantly with the time of TT for all the investigated samples, although with different behaviors. The core-shell samples with Yb3+ in the shell, even those ones with a second undoped shell, showed a reduction in the emissions for 180 minutes of TT compared to those for 90 minutes of TT. This is an indication of the TT effect on the surface making the Yb3+ ion, which is an excellent energy donor, interacts more with the surface of the nanocrystals. On the other hand, the samples only core, co-doped with Yb/Er, exhibited similar emission for TT of 90 and 180 minutes, most likely because there is less competition between the energy transfer from Yb3+ to Er3+ than from Yb3+ to surface impurities. We can say, therefore, that the optimized time of TT at 500 oC is 90 minutes, including for the near-infrared emission from Er3+ ions at 1550 nm. In relation to the Eu3+ doped samples, the best TT times were: from 30 minutes for core samples and 180 minutes for core-shell. For Nd3+ doped samples, the core-shell showed a more regular evolution, likely due to the shielding effect of the shell. It was also noted the similarity of the emission intensities for samples under TT for 90 and 180 minutes for both set of samples (core and core-shell). Therefore, the TT at 500 oC during 90 minutes is sufficient to obtain the desired effect of removing impurities and increasing the Nd3+ emission. Finally, it is important to say that other measures are necessary for a better understanding of what is occurring on the surfaces of nanoparticles and they should be done soon.